Implementasi Kebijkaan Bantuan Operasional Keluarga Berencana dalam Mendukung Capaian Kesertaan Keluarga Berencana (KB) di Kabupaten Subang - Dedi, Dedi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The Operational Assistance for Family Planning (BOKB) is a government policy aimed at supporting the Population and Family Planning programs in regions, funded by the central government through DAK Family Planning Sub-sector funds. This study aims to understand the implementation of the Operational Assistance for Family Planning policy in supporting the achievement of family planning participation in Subang Regency and to identify and analyze the factors influencing policy implementation. Using a phenomenological approach, this research applies a mixed-methods methodology, combining quantitative and qualitative research methods simultaneously to obtain a comprehensive picture of the studied phenomenon. Emphasizing qualitative methods, the researcher concludes that the policy implementation has not met expectations. Indicators of this include the still low level of family planning participation and the suboptimal budget absorption. These issues are influenced by several factors, including the low ability of officers to communicate and provide family planning counseling, the low quality of human resources affected by educational factors, and the resulting low disposition of implementers. Recommendations include increasing resource availability, strengthening coordination between agencies, enhancing education and public awareness, conducting regular monitoring and evaluation, ensuring budget transparency and accountability, and fostering cross-sector collaboration. Keywords: Communication, Disposition, Implementation, Policy, Resources.